Pengaruh Affiliate Marketing, Content Quality, dan Electronic Word of Mouth terhadap Purchase Decision Skincare Skintific oleh Gen Z pada TikTok Shop di Jabodetabek - Amanda Chrisanty Wibowo; Annisa Lutfia; Daru Putri Kusumaningtyas (Indo Publishing, 2026)
This study aims to analyze the influence of Affiliate Marketing, content quality, and electronic word of mouth on purchase decision of Skintific skincare products by Generation Z on TikTok Shop in Jabodetabek. A quantitative approach with a survey method was employed in this study. The population was Generation Z residing in Jabodetabek who had purchased Skintific products through TikTok Shop. A sample of 200 respondents was selected using purposive sampling technique. Data were collected through a questionnaire with a six-point Likert scale. Data analysis techniques included validity test, reliability test, normality test, heteroscedasticity test, simple linear regression analysis, t-test, and coefficient of determination test using IBM SPSS Statistics version 25. The results showed that Affiliate Marketing had a positive and significant effect on purchase decision (sig. 0.000; R² 22.1%), content quality had a positive and significant effect (sig. 0.000; R² 13.1%), and electronic word of mouth had a positive and significant effect (sig. 0.000; R² 26.2%). It can be concluded that all three variables have a positive and significant effect on purchase decision of Skintific products by Generation Z on TikTok Shop in Jabodetabek, with electronic word of mouth providing the greatest contribution.